Life Cycle Cost Structure of a Government Office Green Building – Case of the Ministry of Public Works and Housing Main Building - Domenico Adi Nugroho; Hitapriya Suprayitno; Tri Joko Wahyu Adi (Journal of Infrastructure & Facility Asset Management, 2020)
One of the efforts to reduce the large impact of building sectors on the environment is the concept of environmentally friendly building known as green buildings. With the increasing global interest in this concept, green building development in Indonesia was also expected to increase. Cost is one of the most important focus for promoting green buildings, so it is necessary to conduct a cost analysis of a green building to provide a clearer understanding of the life cycle cost structure of a green building in its life cycle as a study to develop the knowledge of Infrastructure Asset Management. In this study data related to the cost component of the government office green building was identified to determine the overall cost of the building from the beginning of its construction until recent year, which can be described as: Initial Cost, Operation and Maintenance Cost, and Energy Cost. The result of this study finds out that during 8 year period of its lifetime the total building expenditure is Rp 483.649.711.849,00 and the life cycle cost structure percentage are: initial cost 43,94%, operation and maintenance cost 39,48%, and energy cost 16,57%. The total energy cost saving is Rp 28.072.536.738,00.